2017
DOI: 10.3390/md15010023
|View full text |Cite
|
Sign up to set email alerts
|

Klyflaccicembranols A–I, New Cembranoids from the Soft Coral Klyxum flaccidum

Abstract: New cembranoids klyflaccicembranols A–I (1–9), along with gibberosene D (10), have been isolated from the organic extract of a Formosan soft coral Klyxum flaccidum. Their structures were established by extensive spectroscopic analyses, including 2D NMR spectroscopy, and spectral data comparison with related structures. The cytotoxicity of the isolated metabolites, as well as their nitric oxide (NO) inhibitory activity, were evaluated and reported. Metabolites 2, 4, 6, 8 and 9 were found to exhibit variable act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Klyflaccicembranol F ( 11 ): colorless oil; −76 ( c 1.28, CHCl 3 ); lit. −32 ( c 0.60, CHCl 3 ); MS, 1 H and 13 C NMR data were found to be in full agreement with literature data [ 15 ].…”
Section: Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Klyflaccicembranol F ( 11 ): colorless oil; −76 ( c 1.28, CHCl 3 ); lit. −32 ( c 0.60, CHCl 3 ); MS, 1 H and 13 C NMR data were found to be in full agreement with literature data [ 15 ].…”
Section: Methodssupporting
confidence: 86%
“…The EtOAc extract of Sarcophyton glaucum was repeatedly separated by column chromatography and HPLC to obtain five new isoprenoids 1 ‒ 5 and ten known compounds 6 ‒ 15 ( Figure 1 ). By comparing with data in the literature, the known compounds were identified as sarcophine ( 6 ) [ 11 ], lobocrasol ( 7 ) [ 12 ], 3,4-dihydro-4α-hydroxy-Δ 2 -sarcophine ( 8 ) [ 11 , 13 ], 3,4-dihydro-4β-hydroxy-Δ 2 -sarcophine ( 9 ) [ 11 , 13 ], crassumol A ( 10 ) [ 14 ], klyflaccicembranol F ( 11 ) [ 15 ], sarcomilasterol ( 12 ) [ 16 ], sarcoaldesterol B ( 13 ) [ 17 ], sarglaucsterol ( 14 ) [ 18 ], loliolide ( 15 ) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the remaining two unsaturations indicated that compound 1 was a bicyclic diterpenoid. Similar to cembranoids [32], the 1 H NMR of 1 , in conjunction with the heteronuclear single quantum coherence (HSQC) spectrum, revealed the presence of six exocyclic carbons of isopropyl [ δ H 0.97 (3H, d, J = 7.0 Hz), 0.90 (3H, d, J = 7.0 Hz), and 2.21 (1H, sept, J = 7.0 Hz)], two tertiary methyl [ δ H 1.05 and 0.99 (each 3H, s), and α-methylene [ δ H 4.95 and 4.93 (each 1H, s)] groups (Table 2). The analysis of correlation spectroscopy (COSY) of 1 indicated four partial structures bearing consecutive proton systems (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, cembranoid-derived diterpenoids are considered to be the main chemical defense of coral against natural predators [18]. Our previous investigation on the chemical constituents of soft corals belonging to the genus Klyxum [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] has shown a wealth of unique secondary metabolites, including cembrane- and eunicellin-based diterpenoids, and steroids. In this context, we isolated a series of cembrane-diterpenoids [32] and steroids [29,31,33] from the Formosan soft corals Klyxum flaccidum , some of which have been found to possess cytotoxic and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some structurally complex biscembranes derived from Diels–Alder reaction also have been unveiled [ 9 , 10 , 11 ]. Recently, many cembranoids possessing new structures have been isolated from soft corals [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Accordingly, more cembranoids with promising bioactivities have been reported [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%